Chemometrics‐Based Aroma Profiling Reveals Changes in Citrus limon L. Peels During Drying: Advances in Monitoring Lemon Essence - Zemni, Hassène; Lamine, Myriam; Attia, Jihène; Mankaï, Melika; Khiari, Ramla; Jallouli, Selim; Salem, Asma Ben (Flavour and fragrance journal, 2025)
Volatile compounds produce the aroma of fruits such as Citrus limon and play a key role in fruit quality. Moreover, drying technology plays a significant role in aroma quality. To reflect the volatile differences and the dynamic change of volatile profiles of dried lemon peel as affected by drying methods, the volatile compounds of dried peel prepared under three drying methods were analysed by gas chromatography–mass spectrometry combined with chemometrics. According to the results, drying at 35°C allowed to obtain peels with high titratable acidity, high flavonoid content and high antioxidant activity. On the other hand, vacuum freeze drying allowed to obtain samples with high total soluble solids and highest polyphenol contents. Eight volatile compounds were identified, with beta‐and alpha‐pinene and limonene found to play an important role in the discrimination of the different drying processes, based on variable importance in projection ≥ 1.2. These substances might be responsible for what caused the significant flavour difference between differently dried peel flours. The combination of HS–GC–MS and chemometrics offers a valuable tool for the identification of type‐specific volatile markers in lemon peels. This study provided an important study for the improvement of processing and design technology and quality enhancement of C. limon peels, in order to meet consumer demand.